COST AND PRODUCTIVITY ANALYSIS OF THE MANUFACTURING INDUSTRY USING TDABC & MOST - Ganorkar, Ashwin Bhimrao; Lakhe, Ramesh R; Agrawal, Kamalkishor N (The South African Journal of Industrial Engineering, 2019)
Costing is important for manufacturing industries. Large methods of costing have evolved over time. Recently, the time-driven activity- based costing (TDABC) system has gained importance and application. This article describes the procedure that allows companies to implement TDABC using the Maynard operation sequence technique (MOST) for improving productivity and profitability. Two parameters are required for TDABC: (1) the unit cost of supplying capacity, and (2) the time required to perform a transaction or an activity. MOST is employed to estimate the time required for each activity. Based on this, time equations are formulated and the practical capacity of activities is determined. The procedure is explained with the help of a case study from a manufacturing industry. The results of the case study are discussed from the perspective of the overall company and also at the product level. This approach provides the capacity analysis and the cost analysis together with its hierarchical decomposition. This paper also discusses the different information obtained from TDABC, and its usefulness for managers and decision-makers.